The ebb and flow of the fortunes of African studies at the University of Cape Town: an overview - Ntsebeza, Lungisile (Social dynamics, 2020)
This article is an overview of African Studies at the University of Cape Town (UCT). Its main conclusion is that the University has so far failed to put the issue of African Studies high on its agenda. This is by no means a detailed account of the evolution of the concept of African Studies at UCT, but rather an overview that is meant to stimulate debate and discussion as UCT commemorates a centenary of African Studies. The article shows how UCT dealt with the notion of African Studies. In the period leading to the introduction of apartheid in South Africa UCT saw its role as providing resources to those tasked with the formulation and implementation of a "Native policy". With the advent of apartheid, African Studies focused internally on the study of Africa and its people. This provides the backdrop to the debates of the late 1990s involving Mahmood Mamdani, which centred on the teaching of Africa in an African university. I wrap up this article by sounding a clarion call for UCT to put African Studies high on its agenda if it is serious in fulfilling its mission of making UCT a truly African university.